Experimental and modelling studies of carbon dioxide adsorption by porous biomass derived activated carbon - Rashidi, N.A. (Springer Verlag, 2014)
The goal of the study was to produce a low-cost activated carbon from agricultural residues via single stage carbon dioxide (CO2) activation and to investigate its applicability in capturing CO2 flue gas. The performance of the activated carbon was characterized in terms of the chemical composition, surface morphology as well as textural characteristics. The adsorption capacity was investigated at three temperatures of 25, 50 and 100C for different types of adsorbate, such as purified carbon dioxide and binary mixture of carbon dioxide and nitrogen. The purified CO2 adsorption study showed that the greatest adsorption capacity of the optimized activated carbon of 1.79 mmol g-1 was obtained at the lowest operating temperature. In addition, the adsorption study proved that the adsorption capacity for binary mixtures was lower due to the reduction in partial pressure. The experimental values of the purified CO2 adsorption were modelled by the Lagergren pseudo-first-order model, pseudo-second-order model, and intra-particle diffusion model. Based on the analysis, it inferred that the adsorption of CO2 followed the pseudo-second-order model with regression coefficient value higher than 0.995. In addition, the adsorption study was governed by both film diffusion and intra-particle diffusion. The activation energy that was lesser than 25 kJ mol-1 implied that physical adsorption (physisorption) occurred. Â© Springer-Verlag Berlin Heidelberg 2014.